The Zonation of Aridity Intensity in Iran Using Hargreaves- Samani Evapotranspiration Model Based on Digital Elevation Model (DEM) - Taghi Tavoosi; Mohammadreza Mansouri Daneshvar; Alireza Movaqqari (جغرافیا و پایداری محیط)
Due to the long distance from moisture sources and having more radiation exposure, the rate of evapotranspiration in dry regions is more than the annual precipitation. Evapotranspiration rates have proved to be good indicators in estimating the severity of aridity in a region. because of the lesser errors of this method and the lack of recorded climatic parameters in many synoptic stations in Iran, In this study the Hargreaves – Samani method has been used to evaluate the evapotranspiration for 48 synoptic stations in Iran to calculate the evapotranspiration. Then, the spatial analysis was done based on DEM in GIS environment to produce the evapotranspiration maps. Finally, the results integrated to produce the zonation map of intensity aridity in Iran. The results in seasonal and monthly scale showed that the intensity of evapotranspiration was acceptable in conformity with dominated air masses during different seasons in Iran. The Combination of the produced evapotranspiration maps for mean scale of 12 months in 30 years time period revealed that all of the different regions of iran are located in the dry climatic condition since in all of these regions evapotranspiration rate is more than rainfall at least in three months of a year. The accuracy of the results with more intensity is confirmed in the northern and southern coasts of the country and for the central plateau of Iran.